2006
DOI: 10.1093/annonc/mdl077
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor receptor 1 (IGFR-1) is significantly associated with longer survival in non-small-cell lung cancer patients treated with gefitinib

Abstract: IGFR-1 expression and loss of PTEN are not associated with intrinsic resistance to gefitinib. Clinical relevance of these two biomarkers as determinant for acquired resistance, and the prognostic role of IGFR-1 expression in patients not exposed to TKIs should be evaluated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 40 publications
4
65
1
Order By: Relevance
“…Although EGFR is suppressed by gefitinib, the compensatory and continuous activation of PI3K/Akt by enhancing insulin-like growth factor receptor signaling has also been shown to contribute to the acquired gefitinib resistance in wtEGFR-expressing cancer cells (16). Specifically, increased activity of insulin-like growth factor receptor through down-regulation of insulin-like growth factor-binding proteins maintains PI3K/Akt-mediated survival signaling in response to acquired gefitinib resistance in gefitinib-sensitive and wtEGFR-expressing cancer cells (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EGFR is suppressed by gefitinib, the compensatory and continuous activation of PI3K/Akt by enhancing insulin-like growth factor receptor signaling has also been shown to contribute to the acquired gefitinib resistance in wtEGFR-expressing cancer cells (16). Specifically, increased activity of insulin-like growth factor receptor through down-regulation of insulin-like growth factor-binding proteins maintains PI3K/Akt-mediated survival signaling in response to acquired gefitinib resistance in gefitinib-sensitive and wtEGFR-expressing cancer cells (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the well characterized studies between EGFR mutation and gefitinib sensitivity (5)(6)(7)(8), a few studies have addressed the molecular determinants accounting for the cellular sensitivity to gefitinib in wtEGFR-expressing cancer cells. In a cell culture system with acquired resistance to gefitinib, an increased activity of insulin-like growth factor receptor by down-regulating insulin-like growth factor-binding proteins has been found to maintain the PI3K/Akt-mediated survival signaling in response to acquired gefitinib resistance in gefitinib-sensitive and wtEGFR-expressing cancer cells (16,17). In addition, it has also been reported that a non-smoking female NSCLC patient with wtEGFR expression developed acquired gefitinib resistance without any identifiable EGFR mutations (18).…”
mentioning
confidence: 99%
“…For example, EGFR-amplified cells with loss of PTEN exhibit resistance to EGFR inhibitors, even though inhibiting EGFR led to down-regulation of ERK signaling (27). Some studies, for example in NSCLC and breast cancer, have suggested that IGF-1R expression is associated with improved survival, suggesting that the relationship of the IGF-1R system to outcome is more complex than initially thought (28). The mechanism of the IGF-1R pathway involvement in cellular resistance to gefitinib remains unclear.…”
Section: A B Discussionmentioning
confidence: 99%
“…Therefore, MMAC1/PTEN downregulation and Akt activation are likely to associated with acquired resistance to erlotinib. However, Cappuzzo et al 55 evaluated PTEN expression in 93 cases of NSCLC and found that loss of PTEN was detected in 19 tumors (20.4%) and was not associated with any clinical or biological characteristic. These data indicate that loss of PTEN is not associated with intrinsic resistance to gefitinib or erlotinib.…”
Section: Acquired Resistance To Tkismentioning
confidence: 99%
“…Therefore, clinical studies suggest that IGFR-1 expression is not associated with intrinsic resistance to TKIs. 55 However, it is possible that IGFR-1 expression may be relevant to acquired resistance, as demonstrated in the following preclinical models, although no clinical data has been reported.…”
Section: Acquired Resistance To Tkismentioning
confidence: 99%